2015
DOI: 10.1088/2041-8205/802/2/l21
|View full text |Cite
|
Sign up to set email alerts
|

On Flare Predictability Based on Sunspot Group Evolution

Abstract: The forecast method introduced by Korsós et al. (2014) is generalised from the horizontal magnetic gradient (G M ), defined between two opposite polarity spots, to all spots within an appropriately defined region close to the magnetic neutral line of an active region. This novel approach is not limited to searching for the largest G M of two single spots as in previous methods. Instead, the preflare conditions of the evolution of spot groups is captured by the introduction of the weighted horizontal magnetic g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 18 publications
2
38
0
1
Order By: Relevance
“…We investigate the preflare behavior of the simulated 3D δ-type sunspot with the tool put forward by Korsós et al (2015). Namely, they introduced the weighted horizontal magnetic gradient proxy (denoted as WG M ) between two opposite magnetic polarity umbrae in a δ-spot and demonstrated that the WG M could be successfully applied to identifying preflare patterns above the M5 energetic flare class.…”
Section: Implementation Of the Wg M Methodsmentioning
confidence: 99%
“…We investigate the preflare behavior of the simulated 3D δ-type sunspot with the tool put forward by Korsós et al (2015). Namely, they introduced the weighted horizontal magnetic gradient proxy (denoted as WG M ) between two opposite magnetic polarity umbrae in a δ-spot and demonstrated that the WG M could be successfully applied to identifying preflare patterns above the M5 energetic flare class.…”
Section: Implementation Of the Wg M Methodsmentioning
confidence: 99%
“…An accurate variation of probability should include simultaneous parallel methods (and parameters) for which the two proxies suggested above may be helpful, among (or complementary to) other methods. In the future, we would like to automate the identification of the weighted horizontal magnetic gradient applied by Korsós et al (2015a). Therefore, here we have tried to find more reliable forecast parameters that could narrow down the identification of larger intensity flaring ARs with an associated fast CME.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is promising for flare-forecast perspectives because, when G M starts to decrease after a pronouced maximum, this pattern may be considered to be a warning signal of eruption(s). Later, the method of Paper I was further developed and the weighted horizontal magnetic gradient, or WG M (Korsós et al 2015a), was introduced. This new proxy enables the potential to forecast flares stronger than M5.…”
Section: Classifications Of Morphological Complexitymentioning
confidence: 99%
See 2 more Smart Citations